Effect of Lactobacillus rhamnosus GG Supplementation on Intestinal Inflammation Assessed by PET/MRI Scans and Gut Microbiota Composition in HIV-Infected Individuals. (1st August 2018) - Arnbjerg, Caroline J.; Vestad, Beate; Hov, Johannes R.; Pedersen, Karin K.; Jespersen, Sofie; Johannesen, Helle H.; Holm, Kristian; Halvorsen, Bente; Fallentin, Eva; Hansen, Adam E.; Lange, Theis; Kjær, Andreas; et al.
Abstract : Background: Alterations in the gut microbiome have been associated with inflammation and increased cardiovascular risk in HIV-infected individuals. The aim of this study was to investigate the effects of the probiotic strain Lactobacillus rhamnosus GG ( LGG ) on intestinal inflammation, gut microbiota composition, and systemic markers of microbial translocation and inflammation in HIV-infected individuals. Methods: This prospective, clinical interventional trial included 45 individuals [15 combination antiretroviral treatment (cART) naive and 30 cART treated] who ingested LGG twice daily at a dosage of 6 × 109 colony-forming units per capsule for a period of 8 weeks. Intestinal inflammation was assessed using 18 F-2-fluoro-2-deoxy-D-glucose positron emission tomography/magnetic resonance imaging ( 18 F-FDG PET/MRI) scans in 15 individuals. Gut microbiota composition (V3–V4 region of the 16s rRNA gene) and markers of microbial translocation and inflammation (lipopolysaccharide, sCD14, sCD163, sCD25, high-sensitive CRP, IL-6, and tumor necrosis factor-alpha) were analyzed at baseline and after intervention. Results: At baseline, evidence of intestinal inflammation was found in 75% of the participants, with no significant differences between cART-naive and cART-treated individuals. After LGG supplementation, a decrease in intestinal inflammation was detected on PET/MRI (−0.3 mean difference in the combined activity grade score from 6 regions, P = 0.006), along with a reduction of Enterobacteriaceae ( P = 0.018) and Erysipelotrichaceae ( P = 0.037) in the gut microbiome, with reduced Enterobacteriaceae among individuals with decreased 18 F-FDG uptake on PET/MRI ( P = 0.048). No changes were observed for soluble markers of microbial translocation and inflammation. Conclusions: A decrease in intestinal inflammation was found in HIV-infected individuals after ingestion of LGG along with a reduced abundance of Enterobacteriaceae, which may explain the local anti-inflammatory effect in the gut. Abstract : Supplemental Digital Content is Available in the Text.